Characterization, Identification and Evaluation of Wheat-Aegilops sharonensis Chromosome Derivatives - Wang, Xiaolu; Yu, Zhihui; Wang, Hongjin; Li, Jianbo; Han, Ran; Xu, Wenjing; Li, Guangrong; Guo, Jun; Zi, Yan; Li, Faji; Cheng, Dungong; Liu, Aifeng; et al. (Frontiers in Plant Science, 2021)
Aegilops sharonensis, a wild relative of wheat, harbors diverse disease and insect resistance genes, making it a potentially excellent gene source for wheat improvement. In this study, we characterized and evaluated six wheat-A. sharonensis derivatives, which included three disomic additions, one disomic substitution + monotelosomic addition and two disomic substitution + disomic additions. A total of 51 PLUG markers were developed and used to allocate the A. sharonensis chromosomes in each of the six derivatives to Triticeae homoeologous groups. A set of cytogenetic markers specific for A. sharonensis chromosomes was established based on FISH using oligonucleotides as probes. Molecular cytogenetic marker analysis confirmed that these lines were a CS-A. sharonensis 2Ssh disomic addition, a 4Ssh disomic addition, a 4Ssh (4D) substitution + 5SshL monotelosomic addition, a 6Ssh disomic addition, a 4Ssh (4D) substitution + 6Ssh disomic addition and a 4Ssh (4D) substitution + 7Ssh disomic addition line, respectively. Disease resistance investigations showed that chromosome 7Ssh of A. sharonensis might harbor a new powdery mildew resistance gene, and therefore it has potential for use as resistance source for wheat breeding.